Trauma systems: the potential impact of a trauma divert policy on a regional ambulance service. Issue 5 (23rd July 2011) - Moy, Ross; Han, Kyee; Smith, G Dean; Henning, Jeremy
Abstract : Introduction: Recent initiatives in the Care of the Trauma patient in the UK have led to the establishment of Major Trauma Centres (MTCs), supporting a Trauma Network. It is envisaged that any person suffering from major trauma will be taken directly to one of these centres, with an expectant increase in survivability and decrease in morbidity. This will have an impact on the Ambulance Service in terms of journey times, and the MTCs in terms of bed days. Whilst these are not 'new' patients to the NHS, they may require a redistribution of funds. Most of the modelling into the effects of this has been carried out in London, which may not be applicable to more rural areas. We therefore determined to gain data on how a similar policy would affect trauma services in our rural region. Method: A retrospective study of all trauma patients conveyed by a regional ambulance service. The London Trauma Divert Criteria were applied to the patient report forms, and the number of patients who may have transported directly (or by secondary transfer) to MTCs identified. Results: We found that between 28 and 58 additional patients a month would be transferred. Conclusion: As this is more than 1 patient a day, there may be considerable strain on the MTCs and Ambulance Services. We believe service commissioners in rural areas need to consider the funding and organisational arrangements for major trauma in light of this.